The Living, Dynamic and Complex Environment Care in Intensive Care Unit (Revista Latino-Americana de Enfermagem, 2015)
;;OBJECTIVE:;; to understand the meaning of the Adult Intensive Care Unit environment of care, experienced by professionals working in this unit, managers, patients, families and professional support services, as well as build a theoretical model about the Adult Intensive Care Unit environment of care.;;;;METHOD:;; Grounded Theory, both for the collection and for data analysis. Based on theoretical sampling, we carried out 39 in-depth interviews semi-structured from three different Adult Intensive Care Units.;;;;RESULTS:;; built up the so-called substantive theory "Sustaining life in the complex environment of care in the Intensive Care Unit". It was bounded by eight categories: "caring and continuously monitoring the patient" and "using appropriate and differentiated technology" (causal conditions); "Providing a suitable environment" and "having relatives with concern" (context); "Mediating facilities and difficulties" (intervenienting conditions); "Organizing the environment and managing the dynamics of the unit" (strategy) and "finding it difficult to accept and deal with death" (consequences).;;;;CONCLUSION:;; confirmed the thesis that "the care environment in the Intensive Care Unit is a living environment, dynamic and complex that sustains the life of her hospitalized patients".;;